Preoperative CA 19‐9 kinetics as a prognostic variable in radiographically resectable pancreatic adenocarcinoma. Issue 3 (20th October 2014) - Brown, Erin G.; Canter, Robert J.; Bold, Richard J.
<x xml:space="preserve">Abstract</x> Background and Objectives Serial levels of CA 19‐9 are correlated with treatment response and survival; however, little is known about CA 19‐9 kinetics in the absence of therapy. We hypothesize that preoperative CA 19‐9 kinetics predict rate of resectability as well as survival. Methods Retrospective review of 72 patients with radiographically resectable pancreatic adenocarcinoma with two pre‐operative CA 19‐9 levels prior to planned pancreaticoduodenectomy. Primary outcome measures were resectability and overall survival. Results Forty‐seven out of 72 patients (65%) had resectable disease. Unresectable patients had higher absolute change in CA 19‐9 than patients with resectable disease (97 U/ml vs. −34 U/ml) as well as higher rate of change (4 U/ml/day vs. −1 U/ml/day). Receiver operating characteristic curves identified predictive thresholds for absolute (≥50 U/ml) and rate of CA 19‐9 change (≥1 U/ml/day) that accurately identified unresectable patients. Survival analysis revealed that a change in CA 19‐9 <50 U/ml and a rate of change <1 U/ml/day predicted improved survival (P = 0.04, P = 0.02); however, for patients with resectable disease, CA 19‐9 changes did not predict survival. Conclusions Preoperative kinetics of CA 19‐9 predict resectable disease for pancreatic cancer. These variables also predict overall survival; however, these do not predict survival for those with resectable disease. J. Surg. Oncol. 2015 111:293–298. © 2014 Wiley Periodicals, Inc.